Strengthening Families: Reforming Addiction Policy for Better Support and Recovery - Zalanda Muniz; Cynthia L Miller (Undergraduate Research Journal for the Human Sciences, 2025)
This policy brief examines the impact of current punitive drug policies on family stability and public health in the United States. Using historical analysis and evidence from domestic and international policy implementations, this research identifies significant shortcomings in the criminalization approach to substance use disorders (SUDs) that has dominated since 1971. The analysis demonstrates that current policies disproportionately affect minority communities, contribute to family separation, and fail to address the root causes of addiction. Three evidence-based policy alternatives are presented: (1) decriminalizing non-violent drug possession while expanding treatment options, (2) implementing harm reduction strategies to mitigate the consequences of the opioid epidemic, and (3) incorporating family-based approaches to addiction treatment. This research concludes that shifting from punitive to treatment-focused approaches would strengthen family stability, reduce incarceration rates, and create more effective pathways to long-term recovery.
Keywords: substance use disorder policy; family preservation; harm reduction strategies; decriminalization; family-based intervention